If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3x + -1y) = 14 (3x * 2 + -1y * 2) = 14 (6x + -2y) = 14 Solving 6x + -2y = 14 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2y' to each side of the equation. 6x + -2y + 2y = 14 + 2y Combine like terms: -2y + 2y = 0 6x + 0 = 14 + 2y 6x = 14 + 2y Divide each side by '6'. x = 2.333333333 + 0.3333333333y Simplifying x = 2.333333333 + 0.3333333333y
| 14-8x=-3x-8 | | -5w-7=-37 | | 75-(-25)= | | 4r=-3+7r | | -70-5= | | -80-(-40)= | | X=320000 | | X=320000 | | (8x^4)(2x^3)= | | t=10+5 | | 17=c+10 | | x+y=320000 | | 5b+6-6b+r=19 | | 3j-8=5j+4 | | 5.4=3s | | x-69=-6x+99 | | -9=-6+3(5-m) | | 7(7x+5)=7(x-1) | | 5x-111=-7x+105 | | x=180-88 | | x+3.5=10.2 | | 2=3x-10 | | 4=14-k | | -2s-14s-5=11 | | -3t+7=-8t-3 | | 2d+d-3=6 | | p-7=-5 | | -4x+9(x-3)=10x+2 | | 20=8(v-90)-52 | | 3n+6=-10n-7 | | -10q-(-19q)-(-8)=17 | | 10-(-4)= |